Acaricide resistance in Tetranychus urticae on cucumber (Cucumis sativus) under protected cultivation - KAUR, PARAMJIT; BHULLAR, MANMEET BRAR (The Indian Journal of Agricultural Sciences, 2019)
The present study was conducted to determine the effects of four acaricides on four different populations of twospotted spider mite, Tetranychus urticae, collected from cucumber (Cucumis sativus L.) under protected cultivation in 2016 and 2017. The statistical differences were found in susceptibility against treated acaricides and between populations collected from different regions of Punjab. The population with a resistance ratio of more than 60-folds with respect to an acaricide was considered as resistant population. Among all tested acaricides, the highest resistance ratio was reported to fenazaquin (62.52 to 212.55 folds) in population collected from Hoshiarpur, Patiala and Bathinda. Low to moderate level of resistance was reported against spiromesifen (3.76 to 32.10 folds). Propargite (14.64 to 22.17 folds) and fenpyroximate (17.10 to 32.10-folds) showed moderate level of resistance in T. urticae. The collected populations of T. urticae on cucumber under protected cultivation showed moderate to very high level of resistance to spiromesifen, propargite, fenpyroximate and fenazaquin, respectively in Punjab.